Kemenangan Pasangan Sherly Tjoanda dan Sarbin Sahe Sebagai Representasi Kelompok Minoritas pada Pemilihan Gubernur dan Wakil Gubernur Maluku Utara 2024 - Mulawarman; Saputra, Ilham; Banggu, Masni; Tusriadi; Amalia, Dea Rizky (Universitas Muhammadiyah Sorong, 2025)
North Maluku Province is a region with high ethnic, religious, and regional diversity, so that political representation from minority groups often faces structural and cultural challenges. Therefore, the success of the Sherly Tjoanda and Sarbin Sahe pair reflects the political dynamics that have undergone significant shifts. This study aims to determine what factors influence the victory of the Sherly Tjoanda and Sarbin Sahe pair as representatives of minority groups in the 2024 North Maluku Gubernatorial Election. Using a qualitative approach with a documentation study type of research, which collects data from publicly available documents. The results of the study show that there are two main factors that contributed to the victory of the pair. First, the personality factor of Benny Laos and Sherly Tjoanda who have a strong influence in society. Benny Laos is perceived as a generous and accomplished leader, while Sherly Tjoanda is known to be active in social activities, especially while accompanying her husband when he served as Regent of the Morotai Islands. Second, the political communication style applied by the Sherly Tjoanda and Sarbin Sahe pair, who utilized political rhetoric, political debates, and campaigns as the main means of reaching voters, also became a strategic factor in winning the political contest. This finding confirms the importance of political personality and communication as determinants of victory for minority candidates in regional head elections.